2012
DOI: 10.1088/0004-637x/760/1/89
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Cool, Accretion-Shock-Generated X-Ray Plasma in Ex Lupi During the 2008 Optical Eruption

Abstract: EX Lupi is the prototype for a class of young, pre-main-sequence stars which are observed to undergo irregular, presumably accretion-generated, optical outbursts that result in a several magnitude rise of the optical flux. EX Lupi was observed to optically erupt in 2008 January, triggering Chandra ACIS Target of Opportunity observations shortly thereafter. We find very strong evidence that most of the X-ray emission in the first few months after the optical outburst is generated by accretion of circumstellar m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…2 The fact that the CO depletion in EX Lup is less than those observed in normal T Tauri and most of those in Herbig Ae stars as well has interesting implications. EX Lup exhibited a large outburst in 2008, when both its optical and X-ray brightness increased by orders of magnitude (Kóspál et al 2008;Teets et al 2012). According to our modeling, both the midplane and the surface temperature increased in the disk during outburst ( Ábrahám et al 2009).…”
Section: Co Depletion In Ex Lupmentioning
confidence: 53%
See 1 more Smart Citation
“…2 The fact that the CO depletion in EX Lup is less than those observed in normal T Tauri and most of those in Herbig Ae stars as well has interesting implications. EX Lup exhibited a large outburst in 2008, when both its optical and X-ray brightness increased by orders of magnitude (Kóspál et al 2008;Teets et al 2012). According to our modeling, both the midplane and the surface temperature increased in the disk during outburst ( Ábrahám et al 2009).…”
Section: Co Depletion In Ex Lupmentioning
confidence: 53%
“…The emerging picture is broadly consistent with the magnetospheric accretion scenario, in which the infalling material reaches the star in hot spots. Indeed, X-ray and UV observations by Grosso et al (2010) and by Teets et al (2012) (Juhász et al 2012). Modeling the spectral energy distribution (SED) based on these data, Sipos et al 2009 andJuhász et al (2012) deduced a modestly flared disk geometry.…”
Section: Introductionmentioning
confidence: 98%
“…Several snapshots over the course of recent outbursts on V1118 Ori and EX Lup involving both XMM-Newton and Chandra CCD cameras showed that the soft X-ray spectral component evolved towards lower flux, as expected while accretion was fading, but the X-ray temperatures are too high for emission from accretion shocks (e.g. Audard et al, 2010;Teets et al, 2012).…”
Section: Accretionmentioning
confidence: 74%
“…While the number of known EXOr and FUOr events is small by itself, even fewer have been observed in X‐rays, and less than a handful have multiple epoch X‐ray data. Several snapshots over the course of recent outbursts on V1118 Ori and EX Lup involving both XMM‐Newton and Chandra C CD cameras showed that the soft X‐ray spectral component evolved toward lower flux, as expected while accretion was fading, but the X‐ray temperatures are too high for emission from accretion shocks (e.g., Audard et al ; Teets et al ).…”
Section: X‐ray Variability From Yso Environmentsmentioning
confidence: 90%
“…While the X-ray lightcurves of EX Ors tend to be correlated with the optical/IR flux, no clear picture has emerged yet for the characteristics and origin of the X-ray emission, and only a handful of objects have been monitored in X-rays. In most of these, the temperature of the Xray emitting gas was found to be too high for being generated in accretion shocks, but see Teets et al (2012) for a different example. An alternative interpretation for the softening of the X-ray emission observed during some optical/IR outbursts is a change in the structure of the X-ray emitting magnetosphere caused by the accretion event (Audard et al 2005).…”
Section: Fuor and Exor Eventsmentioning
confidence: 99%